From figure to figural: Body and incarnation in contemporary film - Benavente, Fran; Salvadó, Gloria (Academic Quarter | Akademisk kvarter, 2010)
Med udgangspunkt i film breder Fran Benavente og Gloria Salvadó blikket ud til et fokus, der også inddrager kunsthistorien. The article From figure to figural: body and incarnation in contemporary film combines an investigation of film and art history of what lies between the visual and the invisible. This investigation includes recent films by directors such as Philippe Grandrieux, Claire Denis, Bruno Dumont, Bertrand Bonello, Catherine Breillat, David Lynch, Harmony Korine and David Cronenberg. This investigation concludes that these films contain what is called amodal perceptions by Daniel N. Stern, and in art the incarnation and its mysteries is one of the motifs used. An older example is Pliny´s description of the production of a death mask in ancient Rome, where a wax impression was taken of the face of the deceased, which stresses the impossibility of making flesh visible.